Scientific Opinion on the safety and efficacy of Ronozyme® HiPhos M/L (6‐phytase) as a feed additive for poultry and pigs - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) and EFSA Panel on Genetically Modified Organisms (GMO) (EFSA Journal)
Abstract The additive Ronozyme® HiPhos M/L is a preparation of 6‐phytase produced by a genetically modified strain of Aspergillus oryzae. It is intended to be used as a zootechnical feed additive for poultry and pigs. The final enzyme preparation contains no cultivable production organisms or recombinant DNA, given the limits of detection. Based on the trials provided, it was concluded that Ronozyme® HiPhos is safe for chickens for fattening, turkeys for fattening, laying hens, weaned piglets and sows when used at the maximum recommended dose. This conclusion can be extended to all poultry species and pigs for fattening. The fermentation product is non‐genotoxic and there are no concerns for consumer safety. It is not an irritant to skin or eye but in the absence of data should be treated as a skin sensitiser. Since the additive is practically dust free, respiratory exposure from the solid preparation is unlikely. The liquid formulation is only used in contained environments. The active substance of Ronozyme® HiPhos M/L is a protein and as such will be degraded/inactivated during the passage through the digestive tract of animals. Therefore, no risks for the environment are expected and no further environmental risk assessment is required. The additive has the potential to improve phosphorus utilization in all poultry at the minimum dose of 500 FYT/kg complete feed, as demonstrated in short‐term trials with chickens and turkeys for fattening, and laying hens. Improved phosphorus utilization was also seen in weaned piglets and pigs for fattening at the minimum dose of 500 FYT/kg complete feed, and at the minimum dose of 1000 FYT/kg complete feed for sows. The use of the additive allows the use of diets with a lower level of inorganic phosphorus, which may in turn reduce the excretion of phosphorus.